Detecting base pair substitutions in DNA fragments by temperature-gradient gel electrophoresis. - Wartell, R M (1990)
A vertical gel electrophoresis apparatus is described which can distinguish DNA fragments differing by single base pair substitutions. The system employs a homogenous polyacrylamide gel containing urea-formamide and a temperature gradient which runs either perpendicular or parallel to the direction of electrophoresis. The temperature-gradient system simplifies several features of the denaturant-gradient system (1) and is relatively inexpensive to construct. Eight homologous 373 bp DNAs differing by one, two, or nine base pair substitutions were examined. DNA electrophoretic mobility changed abruptly with the temperature induced unwinding of DNA domains. GC to AT substitutions at different locations within the first melting domain, as well as an AT to TA transversion were separated with temperature gradients parallel to the electrophoretic direction. The relative stabilities of the DNAs observed in the gels were compared to predictions of DNA melting theory. General agreement was observed however complete correspondence was not obtained.